Mice, myeloid cells, and dengue: a new model for unraveling vascular leakage mysteries - Kurosu, Takeshi; Sakai, Yusuke; Ami, Yasusi; Shimojima, Masayuki; Yoshikawa, Tomoki; Fukushi, Shuetsu; Nagata, Noriyo; Suzuki, Tadaki; Ebihara, Hideki; Saijo, Masayuki (Frontiers in Microbiology, 2024)
Severe dengue is thought to be caused by an excessive host immune response. Methods: To study the pathogenesis of severe dengue, we developed a novel model using LysM Cre + Ifnar flox/flox mice carrying depleted Ifnar expression only in subsets of murine myeloid cells. Results: Although dengue virus (DENV) clinical isolates were not virulent in LysM Cre + Ifnar flox/flox mice, mouse-adapted DV1-5P7Sp and DV3P12/08P4Bm, which were obtained by passaging the spleen or bone marrow of mice, demonstrated 100% lethality with severe vascular leakage in the liver and small intestine. DV1-5P7Sp and DV3P12/08P4Bm harbored five and seven amino acid substitutions, respectively. Infection also induced neutrophil infiltration in the small intestine, and increased expression of IL-6 and MMP-8 and blockade of TNF-α signaling protected the mice, as demonstrated in a previous severe dengue mouse model using C57/BL6 mice lacking both IFN-α/β and IFN-γ receptors. Notably, the new models with DV1-5P7Sp and DV3P12/08P4Bm showed an increased proliferative capacity of the adapted viruses in the thymus and bone marrow. Discussion: These observations suggest that myeloid cell infection is sufficient to trigger cytokine storm-induced vascular leakage. This model can refine the factors involved in the pathology of severe dengue leading to vascular leakage.